Exploring the metabolic features of purple non-sulfur bacteria for waste carbon utilization and single-cell protein synthesis - Naim Rashid (14152125) (2022)
In recent years, single-cell protein (SCP) has been considered a promising aquaculture feed to cope with the growing issue of food security. SCP is derived from microbes including algae, yeasts, and bacteria. Algae and yeasts have been comprehensively studied as SCP sources in the last few years. However, their large-scale application is not yet economical. Recently, the use of purple non-sulfur bacteria (PNSB) has been realized as a sustainable source of SCP. PNSB display unique metabolic features that distinguish them from other SCP sources. They can grow under various light and electron donor/acceptor conditions, can use a variety of low-cost carbon sources, give high substrate yield under their preferred photoheterotrophic growth mode, and demonstrate anti-pathogenic properties. They also use the infrared region of light that enables their straightforward enrichment under non-axenic conditions. Despite the unique characteristics of PNSB, their use as SCP has not been widely reported. This review provides comprehensive knowledge about different factors that influence the quality and quantity of SCP produced from PNSB. The effects of key factors including light, redox conditions, trace metals, carbon substrate, and substrate availability are discussed. Special focus is given to the use of PNSB as SCP in aquaculture and PNSBs concomitant role in improving water quality. This information would expand knowledge and enhance understanding to utilize PNSB as an alternative SCP source for aquaculture feed. Other Information Published in: Biomass Conversion and Biorefinery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s13399-022-03273-8